Factors Affecting Development Social Emotional Children Aged 4-6 years in Wanasaba Lauk Village - nasution, nur kholidah; siti Hidayati (UIN Mataram, 2024)
This research aims to determine the impact of substitute parenting patterns on the social emotional development of children aged 4-6 years in Bale Belek Hamlet, Wanasaba Lauk Village. This thesis aims to find out: first, the parenting style of substitute parents on the social emotional development of children aged 4-6 years in Bale Belek Hamlet, Wanasaba Lauk Village. Second, factors that influence the social emotional development of children aged 4-6 years in Bale Belek Hamlet, Wanasaba Lauk Village. The method in this research uses a qualitative research method with a type of descriptive qualitative research, namely research that obtains a systematic, actual and accurate picture of the facts and developments of individuals as they are. Data collection techniques obtained through observation, interviews and documentation. The data analysis techniques used are data reduction, data presentation, and data verification. Meanwhile, the validity of the data will be strengthened by extending observations, increasing persistence and data triangulation. From the results of research on the impact of surrogate parenting on the social emotional development of children aged 4-6 years, it was found that surrogate parents use parenting patterns, namely: (1) democratic parenting, namely a parenting style that determines the rules but takes into account the child's circumstances and needs so as to shape the child's social-emotional development into being disciplined, honest, studious, self-confident, and good at socializing. (2) permissive parenting style in which the child is given freedom to do whatever he wants. So that permissive parenting patterns shape the social emotional development of children, becoming stubborn, rebellious, always wanting to win on their own, lazy about studying, and lacking discipline and dishonest.